ANALISIS PERATURAN KEPALA BADAN PERTANAHAN NASIONAL RI NO 4 TAHUN 2010 TENTANG TATA CARA PENERTIBAN TANAH TERLANTAR (STUDI KASUS EKS. PABRIK ES DAN GUDANG KOPI DI KELURAHAN BAJAK) - Hendi Sastra Putra (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2020)
Abstract: Neglected land is land that has received rights from the state in the form of property rights, land use rights, building rights, usage rights and administrative rights or the basis for the control of land that is not cultivated, not used or not used according to the circumstances or nature and nature the purpose of granting rights or the basis of their control. Problem formulation What is the role of the Bengkulu City Bureau in controlling abandoned land in the former ice cream factory and coffee store in Bajak Village? Empirical legal research is a legal research method that uses empirical facts derived from human behavior, both verbal behavior from interviews and real behavior that is performed through direct observation. Primary data is data that comes directly from the field and is based on respondents and informants. Secondary data This data comes from literature books, laws and regulations, surfing the Internet and other documents. Determination of the abandoned country in accordance with Article 19 paragraph 1, the percentage of the abandoned land area is divided into the following groups: (a) 100 percent distributed, (b) more than 25 percent to less than 100 percent displaced,, and (d) distributed less than or equal to 25 percent. Sanctions pursuant to Article 23 paragraph 1 must be cleared of land that has been designated as abandoned land within a period of 1 (one) month after the decision on the determination of the abandoned land has been made by the former rights holder of the items located thereon. (2) If the former right holder does not fulfill the obligations mentioned in paragraph 1, the objects on it no longer belong to him and are controlled directly by the state.Keywords: Neglected land; Rights holders; penalty